Modeling the response of a planar silicon detector when measuring the exposure dose rate in the energy range from 5 keV to 10MeV - Dubina, V.N.; Maslov, N.I.; Shlyahov, I.N. (Вопросы атомной науки и техники, 2020)
The main advantages of using silicon semiconductor detectors in dosimetry in comparison with traditional detectors are considered. The shortcomings are analyzed and possible methods for their elimination are proposed. One of the proposed methods makes it possible to increase the efficiency of detecting gamma quantum in the energy range 0.1…10MeV. The requirements are formulated to optimize the design of detectors operating in a wide range of dose rates and gamma radiation energies by computer simulation. Mathematical calculations and computer simulations determine the dosimeter design, materials and thicknesses γ–converter. The mechanisms of modeling the absorbed dose in air and ambient dose in silicon detectors with a thickness of 300 μm, sizes (5×5)mm² and (1.8×1.8)mm², in the range of incident γ–ray energies from 5keV to 10 MeV are presented. Розглянуто основні переваги застосування кремнієвих напівпровідникових детекторів у задачах дозиметрії в порівнянні з традиційними детекторами. Проаналізовано недоліки та запропоновані можливі методи їх усунення. Один із запропонованих методів дозволяє збільшити ефективність реєстрації гамма-квантів у діапазоні енергій 0,1…10 МэВ. Сформульовано вимоги, необхідні для оптимізації конструкції детекторів, які працюють у широкому діапазоні потужностей доз і енергії гамма–випромінювання, методом комп’ютерного моделювання. Проведені математичні розрахунки і комп’ютерне моделювання визначають конструкцію дозиметра, матеріали і товщину γ–конвертера. Наводяться механізми моделювання поглиненої дози в повітрі і амбієнтної дози в кремнієвих детекторах товщиною від 300 мкм, розмірами (5×5)мм² и (1,8×1,8)мм², у діапазоні енергій падаючого γ–випромінювання від 5 кеВ до 10 МеВ. Рассмотрены основные преимущества применения кремниевых полупроводниковых детекторов в задачах дозиметрии по сравнению с традиционными детекторами. Проанализированы недостатки и предложены возможные методы их устранения. Один из предложенных методов позволяет увеличить эффективность регистрации гамма-квантов в диапазоне энергий 0,1…10 МэВ. Сформулированы требования, необходимые для оптимизации конструкции детекторов, работающих в широком диапазоне мощностей доз и энергии гамма–излучения, методом компьютерного моделирования. Проведенные математические расчеты и компьютерное моделирование определяют конструкцию дозиметра, материалы и толщину γ–конвертера. Приводятся механизмы моделирования поглощенной дозы в воздухе и амбиентной дозы в кремниевых детекторах толщиной от 300 мкм, размерами (5×5)мм² и (1,8×1,8)мм², в диапазоне энергий падающего γ–излучения от 5 кэВ до 10 МэВ.